Graphene oxide enwrapped Ag3PO4 composite: towards a highly efficient and stable visible-light-induced photocatalyst for water purification - Liu, Lei. (2013)
A novel graphene oxide (GO) enwrapped Ag3PO4 (GO–Ag3PO4) composite as a visible-light-induced photocatalyst has been fabricated through an ion-exchange method of CH3COOAg and Na2HPO4 in the presence of GO sheets. Scanning electron microscope and X-ray diffraction analysis confirmed that Ag3PO4 particles have been enwrapped by GO sheets. The UV-vis spectra curve of the GO–Ag3PO4 composite showed strong absorbance in the visible light regions. The photocatalytic activity of the composite was evaluated by the degradation of organic dye (AO7) and phenol under visible-light irradiation. The results indicated that this novel GO–Ag3PO4 composite exhibited significantly higher photocatalytic activities and improved stability under visible-light irradiation, compared with bare Ag3PO4. Moreover, the GO–Ag3PO4 composite showed both excellent intrinsic antibacterial and visible-light-induced photocatalytic disinfection activities toward E. coli cells. The possible mechanism for the enhanced photocatalytic properties and antibacterial activity of the GO–Ag3PO4 composite was also discussed. Our finding paves a way to design highly efficient and stable visible-light-induced photocatalysts for the removal of organic pollutants and pathogenic bacteria for water purification.